Parallel computing technologies : 14th International Conference, PaCT 2017 Nizhny Novgorod, Russia, September 4-8, 2017 Proceedings /: 14th International Conference, PaCT 2017 Nizhny Novgorod, Russia, September 4-8, 2017 Proceedings. (2017) - Unknown
No abstract available